Front and Back Stage of Sriwijaya Indralaya University Students Who Overshared on Tiktok - Titis Setia Ningrum; Diana Dewi Sartika; Gita Isyanawulan; Elita Aidillah; Akhmad Syafe’i; Kurnia Asni Sari; Hayana Muslimah (POPULIKA, 2025)
This study aims to discover the phenomenon of oversharing conducted by Sriwijaya Indralaya University students and to understand the reality of the front and back stages of Sriwijaya Indralaya University students. This study used descriptive qualitative research methods and data collection techniques such as interviews, observation, and documentation, and employed phenomenological research strategies. This informant was determined purposively, namely, UNSRI Indralaya students who actively use TikTok. This study uses Erving Goffman's Dramaturgy theory to analyze the results obtained. The results of this study explain that female students share excessively on TikTok, including seeking the attention of TikTok users, and TikTok as a stage for self-image performance. As for the backstage, the female college student who did Oversharing, Including Lifestyle, Daily life, and family background of female college students. Keywords: Front stage; Back stage; Oversharing.